Evidence-based approach to drug therapy of acute uncomplicated otitis media in children and adults - N. L. Kunelskaya; A. Y. Ivoylov; E. V. Garov; E. E. Garova; M. S. Kulagina (Медицинский совет, 2014)
Acute otitis media (AOM) today is one of the most frequent reasons for seeking medical aid among adults and especially children, and a big social and economic challenge asking for immediate solution. According to recent data, every year 709 million new cases of AOM are registered globally, with over half of cases occurring in children under 5 years [1]. 80% of children are assumed to acquire AOM in the first 3 years of life [2]. In Russia, the incidence of AOM is 10 million people per year and 30% of all patients with hearing organ disorders [3].